Use of maximal dosage renin-angiotensin-aldosterone system inhibitors in a real life population of complicated type 2 diabetes – contraindications and opportunities - C. M. Gant; M. M. Oosterwijk; S. H. Binnenmars; G. J. Navis; H. Haverkate; S. J. L. Bakker; G. D. Laverman (BMC Nephrology, 2023)
Abstract Objective Pharmacological inhibition of the renin-angiotensin-aldosterone-system (RAASi) is the cornerstone of hypertension treatment, renoprotection and secondary prevention of cardiovascular disease in patients with type 2 diabetes. Although there is a dose-dependent effect of RAASi with optimum protection when using maximal dose, little is known on actual use of maximal dosage RAASi in clinical practice. Here we investigate prevalence of maximal dosage RAASi, and contraindications for, optimizing RAASi dosage, in patients with complicated type 2 diabetes in a real-life clinical setting. Research design and methods We performed a retrospective analysis in 668 patients included in the DIAbetes and LifEstyle Cohort Twente (DIALECT). We grouped patients according to no RAASi, submaximal RAASi and maximal RAASi use. All potassium and creatinine measurements between January 1st 2000 and date of inclusion in DIALECT were extracted from patients files. We identified determinants of maximal RAASi use vs. submaximal RAASi use with multivariate logistic regression analysis. Results Mean age was 64 ± 10 years and 61% were men. In total, 460 patients (69%) used RAASi, and 30% used maximal RAASi. Maximal RAASi use was not statistically different between different indications for RAASi (i.e. hypertension, diabetic kidney disease, coronary heart disease and cerebrovascular disease; P > 0.05). Per patient, 2 [1-4] measurements of potassium and 20 [13–31] measurements of creatinine were retrieved, retrospective follow-up time was − 3.0 [-1.4 to -5.7] years. Pre-baseline hyperkalemia > 5.0 mmol/l and acute kidney injury were found in 151 (23%) patients and 119 patients (18%), respectively. Determinants of maximal RAASi were prior acute kidney injury (OR 0.51 (0.30–0.87)), increased albuminuria (OR 1.89 (1.17–3.08)) and total number of used antihypertensives (OR 1.66 (1.33–2.06)). Conclusions Maximal dose RAASi is used in almost one third of complicated type 2 diabetes patients in a real-life setting. The prevalence of contraindications is considerable, but relative in nature, suggesting that it is worthwhile to explore strategies aimed at maximizing RAASi while circumventing the alleged contraindications.